Great rollercoaster race (Building the biggest.)
This documentary is about the race to built the great ever rollercoaster in the world. This includes El Toro/Six Flags, Beech Bend Park, and The Voyage rollercoasters. Also discuss about the structures and problem that being face by engineer to built this ultimate rollercoaster.